The piercing–stretching suture technique for the treatment of simple oral floor ranula. Issue 1 (27th January 2022) - Gaffuri, M; Torretta, S; Pignataro, L; Capaccio, P
Abstract: Background: Oral floor ranulas are pseudocysts located in the floor of the mouth that result from the extravasation of mucus from a sublingual gland. Historically, there has been little consensus on the ideal first-line treatment. Currently, definitive treatment involves sublingual gland excision, which can injure the lingual nerve and submandibular duct. Minimally invasive surgical techniques have been proposed, but so far have been associated with a high rate of recurrence. Methods: The so-called piercing–stretching suture technique was performed in 14 naïve adult and paediatric patients (6 females, with a mean age of 20.3 years (range, 7–55 years)). Clinical and ultrasonographic evaluations were performed in all patients; post-operative sialendoscopy was conducted in two paediatric patients. Results: The surgical procedure was successful in all patients, and complete recovery of the ranula was seen in all but one of the patients who underwent suture replacement. No major or minor complications were encountered. Conclusion: This minimally invasive procedure may be considered a reliable and first-line treatment for management of simple oral floor ranulas.